Manfaat Vaksinasi Influenza bagi Pasien Diabetes Melitus - Kurniawan, Rudy; Tahapary, Dicky Levenus (Cermin Dunia Kedokteran, 2024)
People with diabetes mellitus have a dysregulated immune system and are more susceptible to infection, which poses a higher risk of severe influenza complications. Current evidence for influenza vaccine effectiveness in people with diabetes mellitus indicates a beneficial reduction of morbidity and mortality. In addition, serological studies show antibody levels elicited from influenza vaccination in diabetes patients show comparable results with healthy adults. Although more controlled clinical trials in diabetes mellitus patients with influenza are needed to reflect the effect of vaccination, current data indicate the need for routine influenza vaccination in diabetes mellitus patients, as recommended by guidelines. Efforts should be made to increase vaccination coverage in this risk group.